BOOK REVIEW: CORPUS LINGUISTICS AND SECOND LANGUAGE ACQUISITION: PERSPECTIVES, ISSUES, FINDINGS - Samsudin, Samsudin; Sukarismanti, Sukarismanti (LLT Journal: A Journal on Language and Language Teaching, 2024)
This article discusses the application of corpus linguistic methods in second language acquisition (SLA) research. It highlights the significance of utilizing native and learner corpora, along with automated tools for corpus annotation and analysis, to explore various aspects of SLA. The article is based on a book titled "Corpus Linguistics and Second Language Acquisition: Perspectives, Issues, Findings," which covers five chapters. These chapters delve into topics such as variations in L2 usage at a group level, factors influencing L2 processing and production, group-level longitudinal trajectories of L2 development, and inter- and intra-learner variability in L2 development. The book aims to provide valuable insights and methodologies for researchers interested in employing corpus linguistic methods to enhance their SLA research.